(-2x+10)-(6x+5y+12)+(x+8y-16)=

Simple and best practice solution for (-2x+10)-(6x+5y+12)+(x+8y-16)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-2x+10)-(6x+5y+12)+(x+8y-16)= equation:


Simplifying
(-2x + 10) + -1(6x + 5y + 12) + (x + 8y + -16) = 0

Reorder the terms:
(10 + -2x) + -1(6x + 5y + 12) + (x + 8y + -16) = 0

Remove parenthesis around (10 + -2x)
10 + -2x + -1(6x + 5y + 12) + (x + 8y + -16) = 0

Reorder the terms:
10 + -2x + -1(12 + 6x + 5y) + (x + 8y + -16) = 0
10 + -2x + (12 * -1 + 6x * -1 + 5y * -1) + (x + 8y + -16) = 0
10 + -2x + (-12 + -6x + -5y) + (x + 8y + -16) = 0

Reorder the terms:
10 + -2x + -12 + -6x + -5y + (-16 + x + 8y) = 0

Remove parenthesis around (-16 + x + 8y)
10 + -2x + -12 + -6x + -5y + -16 + x + 8y = 0

Reorder the terms:
10 + -12 + -16 + -2x + -6x + x + -5y + 8y = 0

Combine like terms: 10 + -12 = -2
-2 + -16 + -2x + -6x + x + -5y + 8y = 0

Combine like terms: -2 + -16 = -18
-18 + -2x + -6x + x + -5y + 8y = 0

Combine like terms: -2x + -6x = -8x
-18 + -8x + x + -5y + 8y = 0

Combine like terms: -8x + x = -7x
-18 + -7x + -5y + 8y = 0

Combine like terms: -5y + 8y = 3y
-18 + -7x + 3y = 0

Solving
-18 + -7x + 3y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + -7x + 18 + 3y = 0 + 18

Reorder the terms:
-18 + 18 + -7x + 3y = 0 + 18

Combine like terms: -18 + 18 = 0
0 + -7x + 3y = 0 + 18
-7x + 3y = 0 + 18

Combine like terms: 0 + 18 = 18
-7x + 3y = 18

Add '-3y' to each side of the equation.
-7x + 3y + -3y = 18 + -3y

Combine like terms: 3y + -3y = 0
-7x + 0 = 18 + -3y
-7x = 18 + -3y

Divide each side by '-7'.
x = -2.571428571 + 0.4285714286y

Simplifying
x = -2.571428571 + 0.4285714286y

See similar equations:

| 13h+13(3h)= | | 25-13+x-7+120=135 | | 56+2w=9w | | -2(4x+3)+2x=12 | | t+17=33 | | -7=-5x+3 | | (5^2/3)^3y | | 2.9x+59.9=35.5-9.3x | | 4(2-m)+8m=3 | | X-4+5X=32 | | 2x^6+8x^5+5x^4+7x^3+13x^2+0x+23=0 | | 4+10n-3=4n+49-2n | | c/9=11 | | cos(a)=-1 | | 3/14=x-2/42 | | 8=2+2j | | y-4.5=1 | | v-2.5=5.5 | | 5(x-3)+4x= | | 8-2k=2 | | 3s-17=-21+7s | | 9.7x=-78.57 | | 4x=3-3x | | -14a^0b^7c^6/6a^-5b^7c | | 25x^3/(-5x) | | 44+r=1 | | 2x+5-7=12-19 | | (x)(4x)=100 | | 21/3=-9x | | -9+y=-10 | | -9x=21/3 | | 10x^2-20x-85=0 |

Equations solver categories